Metformin induces lactate accumulation and accelerates renal cyst progression in Pkd1-deficient mice. Issue 10 (19th November 2021) - Chang, Ming-Yang; Tsai, Chung-Ying; Chou, Li-Fang; Hsu, Shen-Hsing; Yang, Huang-Yu; Hung, Cheng-Chieh; Tian, Ya-Chung; Ong, Albert C M; Yang, Chih-Wei
Abstract: Metabolic reprogramming is a potential treatment strategy for autosomal dominant polycystic kidney disease (ADPKD). Metformin has been shown to inhibit the early stages of cyst formation in animal models. However, metformin can lead to lactic acidosis in diabetic patients with advanced chronic kidney disease, and its efficacy in ADPKD is still not fully understood. Here, we investigated the effect of metformin in an established hypomorphic mouse model of PKD that presents stable and heritable knockdown of Pkd1 . The Pkd1 miRNA transgenic mice of both genders were randomized to receive metformin or saline injections. Metformin was administrated through daily intraperitoneal injection from postnatal day 35 for 4 weeks. Unexpectedly, metformin treatment at a concentration of 150 mg/kg increased disease severity, including kidney-to-body weight ratio, cystic index and plasma BUN levels, and was associated with increased renal tubular cell proliferation and plasma lactate levels. Functional enrichment analysis for cDNA microarrays from kidney samples revealed significant enrichment of several pro-proliferative pathways including β-catenin, hypoxia-inducible factor-1α, protein kinase Cα and Notch signaling pathways in the metformin-treated mutant mice. The plasma metformin concentrations were still within the recommended therapeutic range for type 2 diabetic patients. Short-term metformin treatment in a second Pkd1 hypomorphic model ( Pkd1 RC/RC ) was however neutral. These results demonstrate that metformin may exacerbate late-stage cyst growth associated with the activation of lactate-related signaling pathways in Pkd1 deficiency. Our findings indicate that using metformin in the later stage of ADPKD might accelerate disease progression and call for the cautious use of metformin in these patients.